2014
DOI: 10.1575/1912/6752
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy-driven circulation in the Red Sea

Abstract: This thesis explores the buoyancy-driven circulation in the Red Sea, using a combination of observations, as well as numerical modeling and analytical method.The first part of the thesis investigates the formation mechanism and spreading of Red Sea Overflow Water (RSOW) in the Red Sea. The preconditions required for open-ocean convection, which is suggested to be the formation mechanism of RSOW, are examined. The RSOW is identified and tracked as a layer with minimum potential vorticity and maximum chlorofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Based on a high-resolution MITgcm, we investigated the budget of eddy energy sources, redistribution and sink in the Red Sea during different seasons. In the Red Sea, overturning circulation has been reported to Journal of Geophysical Research: Oceans 10.1002/2015JC011589 exhibit a distinct seasonally reversing pattern [Yao et al, 2014a[Yao et al, , 2014bSofianos and Johns, 2003;Zhai, 2014], consequently, eddies are calculated with regards to a climatologically monthly mean of flow to eliminate the seasonally varying signals. Our results agree with Zhan et al [2014] who found that eddy activity has a significant seasonality that peaks in winter and troughs in summer.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a high-resolution MITgcm, we investigated the budget of eddy energy sources, redistribution and sink in the Red Sea during different seasons. In the Red Sea, overturning circulation has been reported to Journal of Geophysical Research: Oceans 10.1002/2015JC011589 exhibit a distinct seasonally reversing pattern [Yao et al, 2014a[Yao et al, , 2014bSofianos and Johns, 2003;Zhai, 2014], consequently, eddies are calculated with regards to a climatologically monthly mean of flow to eliminate the seasonally varying signals. Our results agree with Zhan et al [2014] who found that eddy activity has a significant seasonality that peaks in winter and troughs in summer.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The tilted isopycnal in the central and northern basins generates available potential energy, which, when accompanied with a relatively smaller Richardson number in winter, is likely to be released by triggering baroclinic instability that subsequently form eddies [ Zhan et al ., ]. Eddies generated by such baroclinic instability can balance surface buoyancy loss in a marginal sea [ Visbeck et al ., ; Marshall and Schott , ], and, therefore, have a considerable effect on the buoyancy‐driven circulation in the Red Sea [ Zhai , ]. In contrast, in summer, the entire basin is subjected to a positive net heat flux.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…NEM wind causes counterclockwise circulations and cools the surface waters, causing deep convective mixing, whereas SWM wind causes clockwise circulations and upwelling in the Arabian Sea. At the same time, waters are driven into and out of the Sea of Oman, the Arabian Gulf, and the Red Sea steered by boundaries, with gyres being found in the eastern part of the Sea of Oman, the central southern and northern Arabian Gulf, and in the southern and northern Red Sea [23], as shown in Figure 2. As for the biogeochemical properties, there are two distinct periods of high biological activity that emerge as a result of the semiannual wind reversals associated with the monsoon phenomenon.…”
Section: Background: Northern Indian Ocean (Nio)mentioning
confidence: 99%